KAMPUNG KULINER SEHAT DI KEMANG - Ferdian Ferdian; Suwandi Supatra (Jurusan Arsitektur dan Perencanaan, 2020)
Unhealthy lifestyles, and the tendency of consumption of unhealthy foods/ junk food are the main causes of obesity. Third Place is the main theme of this research discussion. The issue discussed in this study is